ijsr 2019
DOI: 10.36106/8502423
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Acute Intestinal Obstruction: A Hospital Based Study

Abstract: BACKGROUND: Intestinal obstruction is a surgical emergency that causes confusion both in the diagnosis and the management. It is related by important disease and mortality. The goal of this study was to classify the etiology, to analyse the methods of performance of acute duodenal obstruction in different age groups, various therapeutic modalities of treatment, to accomplish operative management, anticipate the post-operative complications and outcomes of patients with acute intestinal obstruction. MATERIAL&am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It adversely impacts the lives of millions of individuals, resulting in a considerable healthcare financial load and burden in Africa and beyond. [26][27][28] Abdominal pain is the most common symptom among patients in this review, occurring in over 90% of patients with AMBO. 1,2,4,5 Other symptoms are abdominal distension, vomiting, constipation, obstipation, rectal bleeding, and diarrhea.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It adversely impacts the lives of millions of individuals, resulting in a considerable healthcare financial load and burden in Africa and beyond. [26][27][28] Abdominal pain is the most common symptom among patients in this review, occurring in over 90% of patients with AMBO. 1,2,4,5 Other symptoms are abdominal distension, vomiting, constipation, obstipation, rectal bleeding, and diarrhea.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have also reported wound infection as the most common complication from management of AMBO. 26,27,34,47 6 reported that most cases of wound infection in their study were surgical site infections which resolved with regular dressing while others which were organ abscesses were managed either with ultrasoundguided percutaneous aspiration or by drainage with repeat exploratory laparotomy. Other complications were recurrent adhesions and postoperative enterocutaneous fistula, most of which were reported to resolve on conservative management or repeat exploratory laparotomy.…”
Section: Authormentioning
confidence: 97%